The Digital Self-Efficacy Scale: Adaptation and Validation of Its Spanish Version - Milton Paredes-Aguirre; Ronald Campoverde Aguirre; Olivia Hernandez-Pozas; Yarid Ayala; Holger Barriga Medina (Human Behavior and Emerging Technologies)
The importance of Digital Self-Efficacy is likely to grow as digital technology becomes increasingly widespread. To succeed in today’s digital world, it is essential for people to have a strong belief in their ability to effectively use digital technologies. Therefore, it is necessary for researchers to have adequate instruments to measure them in different populations. The Digital Self-Efficacy Scale offers an innovative technology-independent approach. It provides a multidimensional assessment grounded in the DigComp framework, allowing adaptability and facilitating comparison across diverse demographics. This study examined the validity and reliability of the Spanish-adapted version of the Digital Self-Efficacy for Equatorian workers. The results from a sample of 471 participants, with a gender-balanced distribution (43.74% female and 55.41% male) and a mean age of 34 years, showed that this translated 19-item scale is a valid and reliable measure of this construct. Nomological network analysis with SEM showed that Digital Self-Efficacy had a positive and significant association with task-technology fit and the use of technology. This suggests that workers with higher levels of Digital Self-Efficacy are more likely to use technology effectively and efficiently and that they are more likely to find technology that is a good fit for their tasks.